O sentido do trabalho para mulheres bancárias, pós licença-maternidade, na contemporaneidade - Lick, Ednair Arruda Cardozo (2022)
In contemporary times, the participation of women in the labor market is increasing. They have played relevant roles in the various economic sectors of society. However, they still face difficulties not only in entering a job, but also in maintaining it. Discrimination suffered by women occurs in the most diverse productive sectors. Specifically in the banking sector, differences persist, both related to salaries for the performance of functions like those of men, as well as discrimination when it comes to professional advancement. Added to this, women who return to work after maternity leave start to add to their productive work the responsibility of caring for the child they did not have until then. In addition, they are challenged daily to carry out activities quickly, with quality, in search of results using technologies which control their tasks. As it is a subject little explored in the academy and in the organizational world, the present research aimed to analyze the meaning of work for women in banking, after maternity leave, in contemporary times. Of exploratory qualitative nature, this research brought in the theoretical framework studies that deal with the subject in question, presenting an overview of what has been produced in the academy, with emphasis on the key elements: women in the banking job market, maternity and work and the meanings of work. Oral history was used, through semistructured interviews, with eight women in banking sector from Curitiba (PR) and/or the metropolitan region of this capital, who became mothers and returned to work after maternity leave, between 2019 and 2021 and are employees of a national financial institution. From the collected data, the speeches were transcribed and transformed into first-person narratives and the analysis was based on the interpretive-constructive methodology. The results showed that the work for these women undergoes significant changes after motherhood, changes that range from identifying with what they do, weighing decisions regarding careers, seeking/maintaining a balance between personal and professional life by rethinking priorities. The lack of time for greater dedication to their children and for professional improvement was revealed as an element that causes some anguish to the participants, as well as the feeling of being passed over in processes for professional advancement. As this was a restricted group of women who entered the researched institution through a public tender, for future studies it is recommended to expand to female bank clerks from private institutions. In addition, the main contribution of this study is the reflections on the perceptions of women employees in banking about the meaning of work after maternity leave and that institutions can guarantee to workers who become mothers the possibility of improvement during the workday. Thus, it gives them the opportunity to run for different positions on an equal footing with other people and motherhood is not an exclusion criterion for professional advancement, as revealed in the participants' perception.